Cancer immunogenic cell death via pyroptosis with CXCR4-targeted nanotoxins in hepatocellular carcinoma - Huang, Yingbin; Li, Yihu; He, Rui; Dong, Shuyi; Zhao, Zheng; Jiao, Xingyuan (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Cytotoxic agents have shown limited benefits in hepatocellular carcinoma (HCC), mediated in part by the lack of targeting. As cell-penetrating peptides (CPPs) are capable of delivering various biologically active molecules into cells, including protein, peptides, small chemo-drugs, and nucleic acid with or without targeting, we developed T22-PE24, a CXCR4-targeted self-assembling cytotoxic nanotoxin, to effectively induce HCC pyroptosis. Methods: T22 incorporating EGFP or PE24 was purified from DE3 bacterial cells and characterized using transmission electron microscopy, the Zetasizer Nano®, and SEC-HPLC. The internalization effect of T22-EGFP was detected by FCS in CXCR4+/CXCR4- HCC cells. The CCK8, LDH release, Western blot, and nude mice HCC models were used to estimate the cell viability of T22-PE24. The complete-immunity HCC tumor-bearing mice model was used to assess the immune response of T22-PE24. Results: The round shape under transmission electron microscopy, 49.4 nm hydrodynamic diameter and -33.33 mV zeta potential indicated that T22-PE24 self-assembled into nanoparticles. T22 incorporating EGFP selectively internalized in CXCR4+ HCC cells while showing no accumulation in CXCR4-knockout HCC cells. T22-PE24 nanotoxin induced HCC pyroptosis via the caspase 3/GSDME signaling pathway and suppressed tumor growth in the absence of histological alterations in normal organs. Using the complete-immunity HCC tumor-bearing mice model, we found that T22-PE24 nanotoxin effectively induces the global reprogramming of cell components of the immune tumor microenvironment, leading to enhanced antitumor effects compared to those observed in immunodeficient mice. Conclusion: Our findings demonstrate the activation of the innate immune response in HCC by inducing pyroptosis with T22-PE24 nanotoxin treatment and support an implementation of this strategy for HCC treatment.